Macrovascular Disease in Diabetes: Is the Mouse a Suitable Model? - Müller, O. J.; Katus, H. A.; Backs, J. (Experimental and Clinical Endocrinology & Diabetes, 2012)
To elucidate the pathogenesis of macrovascular disease in diabetes, animal models are widely used. Diabetic mice are of particular interest because they can be crossed to knockout mice lacking specific genes that are under consideration to contribute to diabetic vascular complications. However, the mouse is relative resistant to develop atherosclerosis. Therefore, we review some commonly used mouse models and discuss their advantages and disadvantages.
Keywords: diabetes; cardiovascular incidences; metabolic features